Inventory of macroalgal epiphytes on the seagrass Thalassia testudinum (Hydrocharitaceae) in Parque Nacional Cahuita, Caribbean coast of Costa Rica - Samper Villarreal, Jimena (2008)
Seagrass epiphytes play an important role in seagrass habitats; however, available information from Central America is scarce. The present study focuses on macroalgal epiphytes on leaves of the seagrass Thalassia testudinum in the seagrass meadows at Punta Cahuita, Caribbean coast of Costa Rica, and it is the first one of its kind in Costa Rica. A representative amount for each algal epiphyte species found was collected, preserved and identified to the lowest possible taxon. Preserved samples of each species were deposited in the Herbarium of the Universidad de Costa Rica. A total of 26 species of macroalgae were found: 15 species belonging to Rhodophyta, four to Chlorophyta, six to the class Phaeophyceae, and one diatom species which could not be identified. The present inventory reports three species that are new for the phycological flora of Costa Rica, four species are reported for the first time for the Caribbean coast of Costa Rica, and 17 are new reports for the Parque Nacional Cahuita area. Epiphyte species number might further rise if sampling efforts and the study area increased. Rev. Biol. Trop. 56 (Suppl. 4): 163-174. Epub 2009 June 30.